Mother’s Level Of Knowledge Regarding Self-Medication Practices In Overcoming Skin Problems In Coastal Region - Nurhayati, Nurhayati; Risma, Ade; Panjaitan, Juhri (Universitas Muhammadiyah Semarang, 2025)
Background: Self-medication for skin diseases is common among mothers in coastal areas and is influenced by environmental factors. Understanding maternal knowledge of self-medication is crucial for community health.Objective: This study aims to assess mothers' knowledge level in the coastal area of Secanggang District about self-medication practices for treating skin problems.Methods: A descriptive quantitative research design was used, employing a survey method with face-to-face questionnaire distribution to collect data from 42 mothers residing in Secanggang District. Their questionnaire responses categorized The respondents' knowledge as very good, good, sufficient, poor, or very poor.Results: The study found that 36% of mothers had good knowledge of self-medication, 19% had sufficient knowledge, 11% had poor knowledge, and 34% had very poor knowledge. Boils were identified as the most common skin disease, and Pikangsuang ointment was the most commonly stored medication among respondents.Conclusion: The findings highlight a significant variation in the knowledge levels of mothers regarding self-medication for skin diseases. Enhancing educational initiatives and providing accurate self-medication information can improve coastal communities' health outcomes. Health authorities should focus on targeted educational programs to increase awareness and proper self-medication practices